Toner
By combining binder resin, silica fine particles and fatty acid metal salt in toner particles, the particle characteristics are controlled, and the image degradation and retransfer problems of toner under high-speed conditions are solved, and more stable is achieved image formation and device operation.
Patent Information
- Application Number
- CN202010634400.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-02
- Filing Date
- 2020-07-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-07-02
AI Technical Summary
The existing toners tend to cause image deterioration and retransferring under high-speed conditions, affecting image quality and equipment stability.
Toner particles containing binder resin are used, and external additives include fine silica particles and fatty acid metal salts. By controlling the particle size, coverage and fixation rate, prevent silica from detachment and spreading of fatty acid metal salts, ensuring charging properties. Stablize.
The durability and cleanliness of the toner are significantly improved, prevent retransfer, and maintain image quality and equipment stability.
Smart Images

Figure BDA0002567466950000281 
Figure BDA0002567466950000301 
Figure BDA0002567466950000321
Abstract
Description
Technical Field
[0001] The present invention relates to a toner for developing an electrostatic charge image (electrostatic latent image) used in an image forming method such as electrophotography and electrostatic printing. Background Art
[0002] In recent years, copy machines and printers have been required to have higher speed and higher image quality stability. For toner, high durability that can withstand the high speed and improved stabilization of image quality over a long life are further required.
[0003] As a technology for improving the durability of a toner, Japanese Patent Application Laid-Open No. 2015-141360 discloses a toner in which a thermosetting resin is contained in an encapsulating material having a capsule membrane hardness of 1 N / m or more and less than 3 N / m. The idea is that such a toner can withstand strong shearing.
[0004] Meanwhile, as a method for stabilizing image quality over a long life, it is necessary to remove the toner remaining on the surface of the electrophotographic photosensitive member with a cleaning blade after transfer. For example, it is known that in the case where a fatty acid metal salt is contained in the toner, the fatty acid metal salt acts as a lubricant in the cleaning roller nip portion and can stabilize the cleaning property. Meanwhile, it is also known that filming occurs on the electrostatic latent image bearing member.
[0005] Japanese Patent Application Laid-Open No. 2010-079242 discloses a toner capable of stably improving film formation by using a fatty acid metal salt having a specific particle diameter and particle size distribution. Summary of the invention
[0006] However, it has become clear in recent years that even when the technology disclosed in Japanese Patent Application Laid-Open No. 2015-141360 is used, image degradation such as fogging occurs due to toner degradation.
[0007] It has also become clear that in the recent years of high speed, when the technology disclosed in Japanese Patent Application Laid-Open No. 2010-079242 is used, retransfer occurs as a new problem. Retransfer is a phenomenon in which the toner transferred (primary transfer) from the photosensitive member to the intermediate transfer member in the upstream image forming unit is transferred to the photosensitive member in the downstream image forming unit. This will cause image defects such as a decrease in image density.
[0008] The present invention provides a toner that is more durable than conventional toners, can provide stable cleaning properties by using a fatty acid metal salt, and can prevent re-transfer even when a fatty acid metal salt is used.
[0009] A toner comprising:
[0010] Toner particles containing a binder resin; and
[0011] External additives, including
[0012] The external additives include external additive A and external additive B,
[0013] The external additive A is silica fine particles,
[0014] The external additive B is a fatty acid metal salt,
[0015] The external additive A has a primary particle number average particle size of 5 nm to 25 nm,
[0016] The coverage of the surface of the toner particles by the external additive A is 60% to 80%, and
[0017] The average theoretical surface area of the toner particles obtained by the number average particle size, particle size distribution and true density measured by the Coulter counter is C (m 2 / g), the amount of the external additive B relative to 100 parts by mass of the toner particles is represented by D (parts by mass), and the coverage of the surface of the toner particles by the external additive B is represented by E (%), satisfying the following formulas (1) and (2):
[0018] 0.05≤D / C≤2.00…(1)
[0019] E / (D / C)≤50.0…(2).
[0020] The present invention can provide a toner that is more durable than conventional toners, can provide stable cleaning properties by using a fatty acid metal salt, and can prevent re-transfer even when a fatty acid metal salt is used.
[0021] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION
[0022] Unless otherwise specifically stated, the description of a numerical range such as “from XX to YY” or “XX to YY” etc. in the present invention includes the numerical values at the upper limit and the lower limit of the range.
[0023] The present invention provides a toner, comprising:
[0024] Toner particles containing a binder resin; and
[0025] External additives, including
[0026] The external additives include external additive A and external additive B,
[0027] The external additive A is silica fine particles,
[0028] The external additive B is a fatty acid metal salt,
[0029] The external additive A has a primary particle number average particle size of 5 nm to 25 nm,
[0030] The coverage of the surface of the toner particles by the external additive A is 60% to 80%, and
[0031] When the number average particle size, particle size distribution and the average theoretical surface area of the toner particles measured by a Coulter counter are obtained, the average theoretical surface area is C (m 2 When the amount of the external additive B relative to 100 parts by mass of the toner particles is represented by D (parts by mass), and the coverage of the surface of the toner particles by the external additive B is represented by E (%), the following formulas (1) and (2) are satisfied:
[0032] 0.05≤D / C≤2.00…(1)
[0033] E / (D / C)≤50.0…(2).
[0034] Depending on process conditions, conventional toners containing fatty acid metal salts may not be able to withstand increases in the speed of the developing roller and the speed of stirring the developer due to the speed increase of printers. The reason for this is considered to be as follows.
[0035] Conventional toners generally include external additives such as silica particles in addition to fatty acid metal salts. Fatty acid metal salts are easily deformable and spreadable materials, and when shearing force is applied thereto, the fatty acid metal salt spreads on the surface of the toner particles. At this time, the fatty acid metal salt captures silica. That is, since silica may be detached from the surface of the toner particles, charging becomes uneven, resulting in image defects such as fogging.
[0036] It has been found that conventional toners containing fatty acid metal salts tend to cause retransfer due to the speed increase of printers. The reason for this is considered to be as follows.
[0037] In the case of negatively charged colorant, it is conceivable that when the colorant transferred (first transfer) to the intermediate transfer member in the image forming unit on the upstream side passes through the potential portion of the non-image portion of the photosensitive member in the image forming unit on the downstream side, discharge is generated and the polarity of the colorant is reversed from negative polarity to positive polarity, thereby transferring the colorant to the photosensitive member.
[0038] As described above, for conventional toners using fatty acid metal salts, when the development roller rotation speed and the developer stirring speed are increased, external additives such as silica are easily separated, and there are sites where negative charging is insufficient. It is conceivable that discharge occurs when passing through the potential portion of the non-image portion of the photosensitive member, and the polarity is strongly reversed to a more positive polarity, making retransfer more likely to occur.
[0039] By simultaneously improving both the existence state of silica in which silica is less likely to be captured by the fatty acid metal salt and the existence state of the fatty acid metal salt in which silica is less likely to be detached, the occurrence of retransfer due to a decrease in chargeability can be prevented.
[0040] It is necessary that the coverage rate of the silica particles constituting the external additive A on the surface of the toner particles is 60% to 80%.
[0041] In this range, a state can be produced in which the silica fine particles are close to each other and a state can be produced in which the silica fine particles are less likely to be detached from the toner particle surface by the interaction of van der Waals force.
[0042] The coverage can be maintained within the above range by controlling the mixing conditions of silica.
[0043] When the coverage is less than 60%, the silica particles are separated from each other, the interaction due to the van der Waals force does not work sufficiently, and the silica cannot be sufficiently prevented from detaching from the toner particle surface. When the coverage is greater than 80%, detachment is unlikely to occur, but the fixing performance is deteriorated.
[0044] The coverage is preferably 65% to 75%.
[0045] The number average particle diameter of primary particles of the external additive A needs to be 5 nm to 25 nm. When the number average particle diameter is less than 5 nm, the van der Waals force is too strong, and electrostatic aggregation of the silica fine particles occurs, which promotes separation from the toner particle surface.
[0046] Meanwhile, when the number average particle diameter is greater than 25 nm, the van der Waals force between the toner particle surfaces and the silica fine particles decreases, and the silica fine particles are less likely to detach.
[0047] The number average particle size is preferably 5 nm to 16 nm.
[0048] When the number average particle size, particle size distribution and true density of the toner particles measured by the Coulter counter are obtained, the average theoretical surface area is calculated by C (m 2The amount of the external toner B relative to 100 parts by mass of the toner particles is represented by D (parts by mass), and the coverage of the surface of the toner particles by the external additive B is represented by E (%), satisfying the following formulae (1) and (2):
[0049] 0.05≤D / C≤2.00…(1)
[0050] E / (D / C)≤50.0…(2).
[0051] D / C is an expression that makes it possible to determine the degree to which toner particles are covered with externally added B when the toner particles are spherical, and E / (D / C) is an expression that represents the actual coverage ratio relative to the theoretical coverage ratio.
[0052] D / C needs to be 0.05 to 2.00. When D / C is less than 0.05, a sufficient amount of fatty acid metal salt is not provided, and the cleaning property cannot be improved. Meanwhile, when D / C exceeds 2.00, re-transfer occurs due to poor charging caused by deterioration of toner fluidity. D / C is more preferably 0.05 to 0.80.
[0053] It is important that E / (D / C) should be 50.0 or less. E / (D / C) of 50.0 or less means that the actual coverage is lower than the theoretically calculated coverage and means that the fatty acid metal salt is attached or fixed to the toner particle surface in the form of particles and does not spread thereon.
[0054] When E / (D / C) exceeds 50.0, the fatty acid metal salt is present in a spread state on the toner particle surface due to external addition. In this case, the fatty acid metal salt easily captures and separates the silica fine particles, and re-transfer occurs.
[0055] E / (D / C) is preferably 35.0 or less, more preferably 25.0 or less. Meanwhile, the lower limit is not particularly limited, but is preferably 5.0 or more, more preferably 10.0 or more. E / (D / C) can be controlled by the particle size and particle size distribution of the toner particles, the type and amount of the external additives, and the mixing state of the external additives.
[0056] Average theoretical surface area C(m 2 / g) is preferably 0.6 to 1.5, and more preferably 0.9 to 1.1.
[0057] The amount D of the external additive B is preferably 0.03 to 3.0 parts by mass, and more preferably 0.05 to 1.0 parts by mass relative to 100 parts by mass of the toner particles. The coverage E (%) is preferably 0.3 to 30.0, and more preferably 0.5 to 20.0.
[0058] The fixing rate G of the fatty acid metal salt constituting the external additive B to the toner particles is preferably 10.0% or less. When the fixing rate is 10.0% or less, a state is exhibited in which the fatty acid metal salt is not spread by mixing with the toner particles and cannot be fixed to the toner particles, and detachment of the silica fine particles can be prevented.
[0059] The fixing rate G is more preferably 5.0% or less. The lower limit is not particularly limited, but is preferably 0% or more. The fixing rate G can be controlled by the type and amount of the fatty acid metal salt, and the mixing conditions (temperature, rotation time, etc.) of the fatty acid metal salt.
[0060] The following describes the external additive B. The external additive B is a fatty acid metal salt.
[0061] The fatty acid metal salt is preferably a salt of at least one metal selected from the group consisting of zinc, calcium, magnesium, aluminum, and lithium, etc. In addition, a fatty acid zinc salt or a fatty acid calcium salt is more preferred, and a fatty acid zinc salt is even more preferred. When using them, the effect of the present invention becomes more significant.
[0062] As the fatty acid of the fatty acid metal salt, a higher fatty acid having 8 to 28 carbon atoms (more preferably 12 to 22 carbon atoms) is preferred. The metal is preferably a polyvalent metal having a valency of two or more. That is, the fine particles B are preferably a fatty acid metal salt of a polyvalent metal having a valency of two or more (more preferably divalent or trivalent, more preferably divalent) and a fatty acid having a carbon number of 8 to 28 (more preferably 12 to 22).
[0063] When a fatty acid having a carbon number of 8 or more is used, the generation of free fatty acids is easily suppressed. The amount of free fatty acids is preferably 0.20% by mass or less. When the carbon number of the fatty acid is 28 or less, the melting point of the fatty acid metal salt does not become too high and is less likely to inhibit the fixing performance. Stearic acid is particularly preferred as the fatty acid. The polyvalent metal having a divalent or higher valence preferably includes zinc.
[0064] Examples of the fatty acid metal salt include metal stearates such as zinc stearate, calcium stearate, magnesium stearate, aluminum stearate, and lithium stearate, and zinc laurate.
[0065] The fatty acid metal salt preferably includes at least one selected from the group consisting of zinc stearate and calcium stearate.
[0066] The volume-based median particle size D50s of the fatty acid metal salt is preferably 0.15 μm to 2.00 μm, and more preferably 0.40 μm to 1.30 μm.
[0067] When the volume-based median particle size is 0.15 μm or more, the particle size is appropriate so that the function as a lubricant is improved and the cleaning property is improved. In addition, when the particle size is 2.00 μm or less, the fatty acid metal salt is less likely to accumulate between the developing roller and the restricting blade, and development streaks can be prevented.
[0068] The fatty acid metal salt preferably has a span value B of 1.75 or less as defined by the following formula (3).
[0069] Span value B = (D95s-D5s) / D50s (3)
[0070] Where D5s is the 5% cumulative diameter based on volume of the fatty acid metal salt,
[0071] D50s is the 50% cumulative diameter on a volume basis of the fatty acid metal salt, and
[0072] D95s is the volume-based 95% cumulative diameter of the fatty acid metal salt.
[0073] The span value B is an index indicating the particle size distribution of the fatty acid metal salt. When the span value B is 1.75 or less, the spread of the particle size of the fatty acid metal salt present in the toner becomes smaller, so that better charging stability can be obtained. Therefore, the amount of toner changed to the opposite polarity is reduced, and fogging and retransfer can be suppressed. The span value B is more preferably 1.50 or less because a more stable image is obtained. A more preferred value is 1.35 or less. There is no particular restriction on the lower limit value, but it is preferably 0.50 or more, and more preferably 0.80 or more.
[0074] The external additive preferably includes a hydrotalcite compound.
[0075] By containing the hydrotalcite compound, the separation of silica can be further prevented, and re-transfer and fogging can be prevented.
[0076] The present inventors consider the reason as follows. In the case of a negatively charged toner, the hydrotalcite compound generally has a positive polarity compared to the toner particles and the silica fine particles, and the hydrotalcite compound exerts an adhesive force on both the toner particles and the silica fine particles. Therefore, the silica fine particles are less likely to detach from the toner particles due to the intervention of the hydrotalcite compound.
[0077] In addition, it is considered that the hydrotalcite compound functions as a microcarrier and imparts chargeability to the toner, thereby compensating for poor charging caused by separation of silica fine particles due to the fatty acid metal salt, thus making it possible to prevent re-transfer.
[0078] The amount of the hydrotalcite compound is preferably 0.1 parts by mass to 2.0 parts by mass relative to 100 parts by mass of the toner particles.
[0079] The fixing rate F of the external additive A to the toner particles is preferably 80.0% or more. In this range, it is possible to prevent the fatty acid metal salt from spreading on the toner particle surface when externally added and prevent the external additive A from being captured at that time.
[0080] The fixing rate F is more preferably 85.0% or more. Meanwhile, the upper limit is not particularly limited, but is preferably 95.0% or less. The fixing rate F can be controlled by the mixing process conditions (temperature, rotation time, etc.) and the type of the external additive A (particle size, etc.).
[0081] The relationship between the fixing rate F (%) of the external additive A to the toner particles and the fixing rate G (%) of the external additive B to the toner particles is preferably F / G ≥ 8.0. In this range, the fatty acid metal salt does not spread and is less likely to be fixed to the toner particles, and the detachment of the silica fine particles can be prevented, so that re-transfer can be further prevented.
[0082] More preferably, F / G is 30.0 or more. The upper limit is not particularly limited, but is more preferably 150.0 or less.
[0083] The external additive A is formed of silica fine particles and may be those obtained by a dry method such as fumed silica, or may be those obtained by a wet method such as a sol-gel method, etc. From the viewpoint of chargeability, silica fine particles obtained by a dry method are preferably used.
[0084] In addition, the external additive A may be surface treated for the purpose of imparting hydrophobicity and fluidity. The hydrophobic method can be exemplified by a method of chemically treating with an organosilicon compound that reacts or physically adsorbs with silica fine particles. In a preferred method, silica prepared by gas phase oxidation of a silicon halide is treated with an organosilicon compound. Examples of such organosilicon compounds are listed below.
[0085] Hexamethyldisilazane, trimethylsilane, trimethylchlorosilane, trimethylethoxysilane, dimethyldichlorosilane, methyltrichlorosilane, allyldimethylchlorosilane, allylphenyldichlorosilane, and benzyldimethylchlorosilane.
[0086] Other examples include bromomethyldimethylchlorosilane, α-chloroethyltrichlorosilane, β-chloroethyltrichlorosilane, chloromethyldimethylchlorosilane, triorganosilylmercaptan, trimethylsilylmercaptan, triorganosilylacrylate.
[0087] Further, other examples include vinyldimethylacetoxysilane, dimethylethoxysilane, dimethyldimethoxysilane, diphenyldiethoxysilane, and 1-hexamethyldisiloxane.
[0088] Other examples include 1,3-divinyltetramethyldisiloxane, 1,3-diphenyltetramethyldisiloxane, and dimethylpolysiloxane having 2 to 12 siloxane units per molecule and one hydroxyl group in a terminal unit per Si. These are used alone or in mixture of two or more.
[0089] In the silica treated with silicone oil, preferably the viscosity at 25°C is 30 mm 2 / s to 1000mm 2 / s of silicone oil.
[0090] Examples include dimethyl silicone oil, methylphenyl silicone oil, α-methylstyrene-modified silicone oil, chlorophenyl silicone oil, and fluorine-modified silicone oil.
[0091] The following methods can be used for silicone oil treatment.
[0092] A method in which silica treated with a silane coupling agent and silicone oil are directly mixed using a mixer such as a Henschel mixer.
[0093] A method of spraying silicone oil on silica as a base material. Alternatively, a method of dissolving or dispersing silicone oil in a suitable solvent, then adding silica, mixing, and removing the solvent.
[0094] After the treatment with silicone oil, the silica treated with silicone oil is preferably heated to a temperature of 200° C. or higher (more preferably 250° C. or higher) in an inert gas to stabilize the surface coat.
[0095] A preferred silane coupling agent is hexamethyldisilazane (HMDS).
[0096] In order to improve the properties of the toner, the toner may further include other external additives.
[0097] A preferred preparation method for adding external additives A and B is described below.
[0098] From the viewpoint of controlling the coverage and fixation rate of the external additives, it is preferred to divide the step of adding external additives A and B into two stages. That is, it is preferred to have a step of adding external additive A to toner particles and a step of adding external additive B to toner particles to which external additive A has been added.
[0099] The step of adding the external additives A and B to the toner particles may be a dry method, a wet method, or a two-stage method.
[0100] The external adding device may be heated in the step of adding the external additive A to the toner particles. The temperature is preferably Tg (glass transition temperature of the toner particles) or lower, for example, about 20°C to 50°C.
[0101] The glass transition temperature Tg of the toner particles is preferably 40°C to 70°C, and more preferably 50°C to 65°C, from the viewpoint of storage stability.
[0102] As the device used for the external addition step, a device having a mixing function and a function of imparting mechanical impact force is preferred, and a known mixing treatment device can be used. Examples thereof include FM mixer (manufactured by Nippon Coke Industry Co., Ltd.), SUPER MIXER (manufactured by Kawata Co., Ltd.), and HYBRIDIZER (manufactured by Nara Machinery Co., Ltd.).
[0103] Then, the external toner B is added to the toner particles to which the external additive A has been added. The same apparatus as that used in the external addition step of the external additive A can be used at this time.
[0104] The temperature of the step of adding the external additive B may be, for example, about 20°C to 40°C.
[0105] When a hydrotalcite compound is used, it is preferred that the hydrotalcite compound is added simultaneously with the addition of the external additive B.
[0106] The amount of the external additive A is preferably 0.5 parts by mass to 5.0 parts by mass, and more preferably 1.0 parts by mass to 3.0 parts by mass, relative to 100 parts by mass of the toner particles.
[0107] The method for producing the toner particles is explained. There is no particular limitation on the method for producing the toner particles, and a known method such as a kneading pulverization method or a wet production method can be used. A wet method is preferred to obtain a uniform particle size and control the particle shape. Examples of the wet production method include a suspension polymerization method, a dissolution suspension method, an emulsion polymerization aggregation method, and an emulsion aggregation method, and the emulsion aggregation method is preferably used.
[0108] In the emulsion aggregation method, fine particles of a binder resin and, if necessary, fine particles of other materials such as a colorant are dispersed and mixed in an aqueous medium containing a dispersion stabilizer. A surfactant may also be added to the aqueous medium. A coagulant is then added to aggregate the mixture until the desired toner particle size is reached, and after or during the aggregation, the resin fine particles are melted and attached together. In this method, the shape may also be controlled by heating, if necessary, to form toner particles.
[0109] The fine particles of the binder resin herein may be composite particles formed into multilayer particles containing two or more layers composed of different resins, for example, they may be produced by emulsion polymerization, microemulsion polymerization, or phase inversion emulsion polymerization, or by a combination of multiple production methods.
[0110] When the toner particles contain an internal additive, the internal additive may be contained in the resin fine particles. A dispersion of internal additive fine particles consisting only of the internal additive may also be separately prepared, and then the internal additive fine particles may be aggregated with the resin fine particles at the time of aggregation. Resin fine particles having different compositions may also be added at different times during aggregation and aggregated to prepare toner particles consisting of layers having different compositions.
[0111] The following can be used as dispersion stabilizers:
[0112] For example, inorganic dispersing stabilizers such as tricalcium phosphate, magnesium phosphate, zinc phosphate, aluminum phosphate, calcium carbonate, magnesium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silicon dioxide and aluminum oxide.
[0113] Other examples include organic dispersion stabilizers such as polyvinyl alcohol, gelatin, methyl cellulose, methyl hydroxypropyl cellulose, ethyl cellulose, carboxymethyl cellulose sodium salt, and starch.
[0114] A known cationic surfactant, anionic surfactant or nonionic surfactant can be used as the surfactant.
[0115] Specific examples of the cationic surfactant include dodecylammonium bromide, dodecyltrimethylammonium bromide, dodecylpyridinium chloride, dodecylpyridinium bromide, hexadecyltrimethylammonium bromide and the like.
[0116] Specific examples of the nonionic surfactant include dodecyl polyoxyethylene ether, hexadecyl polyoxyethylene ether, nonylphenyl polyoxyethylene ether, lauryl polyoxyethylene ether, sorbitan monooleate polyoxyethylene ether, styrylphenyl polyoxyethylene ether, monodecanoyl sucrose and the like.
[0117] Specific examples of the anionic surfactant include fatty soaps such as sodium stearate and sodium laurate, and sodium lauryl sulfate, sodium dodecylbenzenesulfonate, and sodium polyoxyethylene (2) lauryl ether sulfate.
[0118] The binder resin constituting the toner is explained below.
[0119] Preferred examples of the binder resin include vinyl resins, polyester resins, etc. Examples of the vinyl resins, polyester resins, and other binder resins include the following resins and polymers.
[0120] For example, monomers of styrene and substituted styrene such as polystyrene and polyvinyl toluene; styrene copolymers such as styrene-propylene copolymers, styrene-vinyl toluene copolymers, styrene-vinyl naphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers and styrene-maleic acid ester copolymers; and polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resins, polyamide resins, epoxy resins, polyacrylic resins, rosin, modified rosin, terpene resins, phenol resins, aliphatic or alicyclic hydrocarbon resins and aromatic petroleum resins, etc.
[0121] These binder resins may be used alone or in combination.
[0122] Examples of polymerizable monomers that can be used in the manufacture of vinyl resins include the following: styrene monomers such as styrene, and α-methylstyrene; acrylic esters such as methyl acrylate, and butyl acrylate; methacrylic esters such as methyl methacrylate, 2-hydroxyethyl acrylate, tert-butyl methacrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid, and methacrylic acid; unsaturated dicarboxylic acids such as maleic acid; unsaturated dicarboxylic acid anhydrides such as maleic anhydride; nitrile vinyl monomers such as acrylonitrile; halogen-containing vinyl monomers such as vinyl chloride; and nitrovinyl monomers such as nitrostyrene, etc.
[0123] The binder resin preferably contains a carboxyl group, and is preferably a resin produced using a polymerizable monomer containing a carboxyl group.
[0124] Carboxyl-containing polymerizable monomers include, for example, the following: vinyl carboxylic acids such as acrylic acid, methacrylic acid, α-ethylacrylic acid and crotonic acid; unsaturated dicarboxylic acids such as fumaric acid, maleic acid, citraconic acid and itaconic acid; and unsaturated dicarboxylic acid monoester derivatives such as monoacryloxyethyl succinate, monomethacryloxyethyl succinate, monoacryloxyethyl phthalate and monomethacryloxyethyl phthalate.
[0125] The polycondensate of the carboxylic acid component and the alcohol component listed below can be used as the polyester resin. Examples of the carboxylic acid component include terephthalic acid, isophthalic acid, phthalic acid, fumaric acid, maleic acid, cyclohexanedicarboxylic acid and trimellitic acid. Examples of the alcohol component include bisphenol A, hydrogenated bisphenol, bisphenol A ethylene oxide adduct, bisphenol A propylene oxide adduct, glycerol, trimethylolpropane and pentaerythritol.
[0126] The polyester resin may also be a polyester resin containing a urea group. It is preferred not to cap the terminal and other carboxyl groups of the polyester resin.
[0127] In order to control the molecular weight of the binder resin constituting the toner particles, a crosslinking agent may also be added during the polymerization of the polymerizable monomer.
[0128] Examples include ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, diacrylates of polyethylene glycol #200, #400 and #600, dipropylene glycol diacrylate, polypropylene glycol diacrylate, polyester diacrylate (MANDA, Nippon Kayaku Co., Ltd.), and acrylic acid in these replaced by methacrylic acid.
[0129] The amount of the crosslinking agent added is preferably 0.001 parts by mass to 15.000 parts by mass per 100 parts by mass of the polymerizable monomer.
[0130] The toner particles preferably include a releasing agent. It is preferred that the toner particles contain an ester wax having a melting point of 60° C. to 90° C. Such a wax is excellent in compatibility with a binder resin, so that a plastic effect can be easily obtained.
[0131] Examples of the ester wax include waxes mainly composed of fatty acid esters, such as palm wax and montanic acid ester wax, etc.; fatty acid esters in which the acid component is partially or completely deacidified, such as deacidified palm wax, etc.; hydroxyl-containing methyl ester compounds obtained by hydrogenation of vegetable oils and fats, etc.; saturated fatty acid monoesters such as stearyl stearate and behenyl behenate, etc.; diesterification products of saturated aliphatic diacids such as dibehenyl sebacate, distearyl dodecanedioate and distearyl octadecane dioate and saturated aliphatic alcohols; and diesterification products of saturated aliphatic diols such as nonanediol dibehenate and dodecanediol distearate and saturated aliphatic monocarboxylic acids.
[0132] Among these waxes, difunctional ester waxes (diester) having two ester bonds in the molecular structure are desirably included.
[0133] The difunctional ester wax is an ester compound of a dihydric alcohol and an aliphatic monocarboxylic acid, or an ester compound of a divalent carboxylic acid and an aliphatic monohydric alcohol.
[0134] Specific examples of the aliphatic monocarboxylic acids include myristic acid, palmitic acid, stearic acid, eicosanoic acid, behenic acid, lignoceric acid, cerotic acid, montanic acid, melissic acid, oleic acid, vaccenic acid, linoleic acid, and linolenic acid.
[0135] Specific examples of the fatty monohydric alcohol include myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, tetracosanol, hexacosanol, octacosanol, and triacontanol.
[0136] Specific examples of the divalent carboxylic acid include butanedioic acid (succinic acid), pentanedioic acid (glutaric acid), hexanedioic acid (adipic acid), heptanedioic acid (pimelic acid), octanedioic acid (suberic acid), nonanedioic acid (azelaic acid), decanedioic acid (sebacic acid), dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanedioic acid, phthalic acid, isophthalic acid, terephthalic acid, and the like.
[0137] Specific examples of the diols include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, 1,16-hexadecanediol, 1,18-octadecanediol, 1,20-eicosandiol, 1,30-triacontandiol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,3-pentanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, spiro glycol, 1,4-phenylene glycol, bisphenol A, and hydrogenated bisphenol A, etc.
[0138] Other release agents that can be used include petroleum waxes and derivatives thereof such as paraffin wax, microcrystalline wax and vaseline, montan wax and derivatives thereof, hydrocarbon waxes obtained by the Fischer-Tropsch method and derivatives thereof, polyolefin waxes and derivatives thereof such as polyethylene and polypropylene, natural waxes and derivatives thereof such as palm wax and candelilla wax, higher fatty alcohols, and fatty acids such as stearic acid and palmitic acid.
[0139] The content of the release agent is preferably 5.0 parts by mass to 20.0 parts by mass relative to 100.0 parts by mass of the binder resin.
[0140] The toner may further contain a colorant. The colorant is not particularly limited, and the following known colorants may be used.
[0141] Examples of yellow pigments include yellow iron oxide, Naples yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, condensed azo compounds such as tartrazine lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include:
[0142] CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168 and 180.
[0143] Specific examples of red pigments include red iron oxide, permanent red 4R, lithol red, pyrazolone red, watching red calcium salt, red lake C, red lake D, brilliant carmine 6B, brilliant carmine 3B, eosin lake, rhodamine lake B, condensed azo compounds such as alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include:
[0144] CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221 and 254.
[0145] Examples of blue pigments include basic blue lakes, Victoria blue lakes, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, copper phthalocyanine compounds such as indathrene blue BG and their derivatives, anthraquinone compounds, and basic dye lake compounds. Specific examples include:
[0146] CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62 and 66.
[0147] Examples of black pigments include carbon black and aniline black. These colorants may be used alone or as a mixture or in the form of a solid solution.
[0148] The content of the colorant is preferably 3.0 parts by mass to 15.0 parts by mass relative to 100.0 parts by mass of the binder resin.
[0149] The toner particles may further contain a charge control agent. A known charge control agent may be used. A charge control agent that provides a fast charging speed and can stably maintain a uniform charge amount is particularly desirable.
[0150] Examples of the charge control agent for controlling the negative chargeability of toner particles include:
[0151] Organometallic compounds and chelate compounds include monoazo metal compounds, acetylacetonate metal compounds, aromatic oxygen-containing carboxylic acids, aromatic dicarboxylic acids, and metal compounds of oxygen-containing carboxylic acids and dicarboxylic acids. Other examples include aromatic oxygen-containing carboxylic acids, aromatic monocarboxylic acids, and aromatic polycarboxylic acids and their metal salts, anhydrides, and esters, as well as phenol derivatives such as bisphenol, etc.
[0152] Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes.
[0153] Meanwhile, examples of charge control agents for controlling the positive charge of toner particles include nigrosin and nigrosin modified with fatty acid metal salts; guanidine compounds; imidazole compounds; quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthalenesulfonate and tetrabutylammonium tetrafluoroborate, onium salts such as phosphonium salts as analogs of these, and lake pigments of these; triphenylmethane dyes and lake pigments thereof (using phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanic acid or ferrocyanide, etc. as laking agents); metal salts of higher fatty acids; and resin charge control agents.
[0154] These charge control agents may be used alone or in combination of two or more thereof. The amount of these charge control agents added is preferably 0.01 to 10.00 parts by mass relative to 100.00 parts by mass of the polymerizable monomer.
[0155] The measurement methods of various physical properties are described below.
[0156] Determination of median particle size and span value of external additive B (fatty acid metal salt)
[0157] The volume-based median diameter of the fatty acid metal salt is measured in accordance with JIS Z 8825-1 (2001), and is specifically as follows.
[0158] As a measuring device, a laser diffraction / scattering type particle size distribution device "LA-920" (manufactured by Horiba, Ltd.) was used. The dedicated software "HORIBA LA-920for WET (LA-920) Ver. 2.02" was used to set the measurement conditions and analyze the measurement data. In addition, ion exchange water from which impurity solids and the like were removed in advance was used as the measurement solvent.
[0159] The measurement process is as follows.
[0160] (1) Attach a batch-type cell holder to the LA-920.
[0161] (2) A predetermined amount of ion exchange water is placed in a batch cell, and the batch cell is set in a batch cell holder.
[0162] (3) Use a special stirrer head to stir the interior of the batch tank.
[0163] (4) Press the "REFRACTIVE INDEX" button on the "DISPLAY CONDITION SETTING" screen and select the file "110A000I" (relative refractive index 1.10).
[0164] (5) On the "Display Condition Settings" screen, set the particle size as the volume basis.
[0165] (6) After performing a warm-up operation for 1 hour or more, perform optical axis adjustment, optical axis fine adjustment, and blank measurement.
[0166] (7) About 60 ml of ion exchange water was placed in a 100 ml flat bottom beaker made of glass. As a dispersant, about 0.3 ml of a dilution solution prepared by diluting "CONTAMINON N" (a 10% by mass aqueous solution of a neutral detergent for cleaning precision measuring instruments; pH 7 and including a nonionic surfactant, an anionic surfactant and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) with about 3 times the mass of ion exchange water was added.
[0167] (8) An ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Inc.) having a power output of 120 W and having two oscillators of a 50 kHz oscillation frequency arranged with a phase shift of 180° from each other was prepared. About 3.3 L of ion-exchanged water was placed in a water tank of the ultrasonic disperser, and about 2 ml of CONTAMINON N was added to the water tank.
[0168] (9) The beaker in (7) is placed in the beaker fixing hole on the ultrasonic disperser, and the ultrasonic disperser is started. Then, the height position of the beaker is adjusted to maximize the resonance state of the liquid surface of the aqueous solution in the beaker.
[0169] (10) While the aqueous solution in the beaker of (9) is irradiated with ultrasonic waves, about 1 mg of a fatty acid metal salt is added little by little to the aqueous solution in the beaker and dispersed. The ultrasonic dispersion treatment is then continued for an additional 60 seconds. In this case, the fatty acid metal salt sometimes floats on the liquid surface as a lump. In this case, the lump is immersed in water by shaking the beaker, and then ultrasonic dispersion is performed for 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to 10° C. to 40° C.
[0170] (11) While being careful not to introduce air bubbles, the aqueous solution in which the fatty acid metal salt is dispersed prepared in (10) is added little by little to the batch cell, and the transmittance of the tungsten lamp is adjusted to 90% to 95%. The particle size distribution is then measured. Based on the obtained volume-based particle size distribution data, the 5% cumulative diameter, 50% cumulative diameter, and 95% cumulative diameter from the small particle size side are calculated.
[0171] The obtained values are represented by D5s, D50s, and D95s, and the span value is determined from these values.
[0172] Method for measuring true density of toner particles
[0173] When measuring the true density, the number average particle diameter, and the like of toner particles in a toner in which an external additive is externally added to the toner particles, the external additive is removed. A specific method is described below.
[0174] A total of 160 g of sucrose (manufactured by Kishida Chemical) was added to 100 mL of ion exchange water and dissolved in a water bath to prepare a concentrated sucrose solution. A total of 31 g of the concentrated sucrose solution and 6 mL of CONTAMINON N were placed in a centrifuge tube to prepare a dispersion. A total of 1 g of toner was added to the dispersion, and lumps of the toner were dispersed with a scraper or the like.
[0175] The centrifuge tube was shaken for 20 minutes in an oscillator ("KM Shaker" manufactured by Iwaki Sangyo Co., Ltd.) under the condition of 350 reciprocating motions per minute. After shaking, the solution was transferred to a glass tube (50 mL) for a swing rotor and centrifuged for 30 minutes at 3500 rpm in a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.). In the glass tube after centrifugation, the toner particles were present in the uppermost layer, and the external toner was present on the aqueous solution side of the lower layer, so that only the toner particles in the uppermost layer were collected.
[0176] In the case where the external additive is not sufficiently removed, centrifugation is repeated as necessary, and after sufficient separation, the toner liquid is dried to collect the toner particles.
[0177] The true density of the toner particles is measured by a dry type automatic densitometer-automatic pycnometer (manufactured by Yuasa Ionics Co., Ltd.) The conditions are as follows.
[0178] Pool: SM pool (10ml)
[0179] Sample volume: about 2.0g
[0180] This measurement method is based on the gas phase displacement method to measure the true density of solids and liquids. Similar to the liquid phase displacement method, it is based on Archimedes' principle, but because gas (argon) is used as the displacement medium, the accuracy of the micropore is high.
[0181] Method for measuring weight average particle diameter (D4) and number average particle diameter (D1) of toner particles
[0182] A "Multisizer (R) 3 Coulter Counter (trade name)" precision particle size distribution analyzer based on the pore resistance method (Beckman Coulter, Inc.) and dedicated "Beckman Coulter Multisizer 3 Version 3.51 (trade name)" software (Beckman Coulter, Inc.) were used. An orifice tube having a diameter of 100 μm was used, and measurement was performed with 25,000 effective measurement channels, and the measurement data was analyzed and calculated.
[0183] The electrolytic aqueous solution used for measurement may be a solution prepared by dissolving special grade sodium chloride in ion exchange water to a concentration of about 1% by mass, such as "ISOTON II (trade name)" (Beckman Coulter, Inc.).
[0184] Before measurement and analysis, set up the dedicated software as follows.
[0185] In the "Change Standard Measurement Method (SOM)" interface of the dedicated software, the total count of the control mode was set to 50,000 particles, the number of measurements was set to 1, and the value obtained using "Standard Particles 10.0 μm" (Beckman Coulter, Inc.) was set as the Kd value. By pressing the "Threshold / Noise Level Measurement" button, the threshold and noise level were automatically set. The current was set to 1600 μA, the gain was set to 2, and the electrolyte was set to ISOTON II (trade name), and a check was entered for "Rinsing of the mouth tube after measurement".
[0186] In the "Pulse to Particle Size Conversion Settings" interface of the dedicated software, the element interval is set to a logarithmic particle size, the particle size element is set to 256 particle size elements, and the particle size range is set to 2 μm to 60 μm.
[0187] The specific measurement method is as follows.
[0188] (1) Place about 200 mL of the electrolyte solution in a 250 mL glass round-bottom beaker dedicated to the Multisizer 3, place it on the sample stage, and stir it counterclockwise at a rate of 24 rps using a stirring rod. Use the "mouth tube flushing" function of the dedicated software to preliminarily remove dirt and bubbles in the mouth tube.
[0189] (2) 30 ml of the same electrolytic aqueous solution was placed in a 100 ml flat-bottom glass beaker, and about 0.3 ml of a dilution solution of "Contaminon N (trade name)" (a 10 mass % aqueous solution of a neutral detergent for cleaning precision measuring instruments, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion exchange water was added.
[0190] (3) A predetermined amount of ion-exchanged water was added to a water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetra 150 (trade name)" (Nikkaki Bios Co., Ltd.) having a power output of 120 W and built with two oscillators having an oscillation frequency of 50 kHz whose phases were shifted by 180° from each other, and about 2 ml of Contaminon N (trade name) was added to the water tank.
[0191] (4) The beaker in (2) is placed in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is started. The height position of the beaker is adjusted to maximize the resonance state of the liquid surface of the electrolytic aqueous solution in the beaker.
[0192] (5) While the electrolytic aqueous solution in the beaker in the above (4) is exposed to ultrasonic waves, about 10 mg of the toner is added little by little to the electrolytic aqueous solution and dispersed. The ultrasonic dispersion is then continued for an additional 60 seconds. During the ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to 10° C. to 40° C.
[0193] (6) Using a pipette, the electrolytic aqueous solution containing the toner particles in (5) above is dropped into the round-bottomed beaker set on the sample stand in (1) above, and the measurement concentration is adjusted to about 5%. Then, measurement is performed until the number of particles measured reaches 50,000.
[0194] (7) The measurement data is analyzed using the dedicated software attached to the equipment, and the weight average particle size (D4) and the number average particle size (D1) are calculated. The weight average particle size (D4) is the "average diameter" on the "analysis / volume statistics (arithmetic mean)" screen when the dedicated software is set to "chart / volume %". The number average particle size (D1) is the "average diameter" on the "analysis / number statistics (arithmetic mean)" screen when the dedicated software is set to "chart / number %".
[0195] Calculation method of average theoretical surface area C per unit mass of toner particles
[0196] After obtaining the number average particle size (D1), the dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (Beckman Coulter, Inc.) is used to divide the range of 2.0 to 32.0 μm into 12 channels (2.000 to 2.520 μm, 2.520 to 3.175 μm, 3.175 to 4.000 μm, 4.000 to 5.040 μm, 5.040 to 6.350 μm, 6.350 to 8.000 μm, 8.000 to 10.079 μm, 10.079 to 12.699 μm, 12.699 to 16.000 μm, 16.000 to 20.159 μm, 20.159 to 25.398 μm, and 25.398 to 32.000 μm), and determine the number ratio of colorant particles in each particle size range.
[0197] Thereafter, using the median value of each channel (for example, when the channel is 2.000 to 2.520 μm, the median value is 2.260 μm), assuming that the toner particle having the median value of each channel is a true sphere, the theoretical surface area (=4×π×(median value of each channel)) is obtained. 2 ). The theoretical surface area is multiplied by the previously determined ratio of the number of particles belonging to each channel to determine the average theoretical surface area (a) of one toner particle assuming that the toner particle being measured is a true sphere.
[0198] Then, the theoretical mass (=4 / 3×π×(median value of each channel)) is obtained from the median value of each channel and the measured true density of the toner particle in the same manner, assuming that the toner particle having the median value of each channel is a true sphere. 3 × true density). The average theoretical mass (b) of one toner particle is determined from the theoretical mass and the ratio of the number of particles belonging to each channel determined above.
[0199] As described above, the average theoretical surface area C (m2) per unit mass of the measured toner particles is calculated from the average theoretical surface area and the average theoretical mass of one toner particle. 2 / g).
[0200] Measuring method of coverage E of external additive B (fatty acid metal salt)
[0201] The coverage of the fatty acid metal salt was measured by ESCA (X-ray Photoelectron Spectroscopy) (Quantum 2000 manufactured by ULVAC-PHI).
[0202] A 75 mm square pressing plate (provided with a screw hole of about 1 mm diameter for sample fixing) attached to the device was used as a sample holder. Since the screw hole of the pressing plate is a through hole, the hole is closed with a resin or the like, and a concave portion for powder determination having a depth of about 0.5 mm is prepared. The concave portion is filled with a measurement sample (toner or external additive B (fatty acid metal salt) alone) using a scraper or the like, and the sample is prepared by grinding.
[0203] The ESCA measurement conditions are as follows.
[0204] Analytical method: Narrow analysis
[0205] X-ray source: Al-Kα
[0206] X-ray conditions: 100μ, 25W, 15kV
[0207] Photoelectron capture angle: 45°
[0208] Pass Energy: 58.70eV
[0209] Measuring range: φ100μm
[0210] First, the toner is measured. In order to calculate the quantitative value of the metal atoms contained in the fatty acid metal salt, C1s (BE 280 eV to 295 eV), O 1s (BE 525 eV to 540 eV), Si 2p (BE 95 eV to 113 eV), and the element peak of the metal atoms of the fatty acid metal salt are used. The quantitative value of the metal element obtained here is represented by X1.
[0211] Then, in the same manner, elemental analysis of the fatty acid metal salt alone was performed, and the quantitative values of the elements contained in the fatty acid metal salt obtained here were represented by X2.
[0212] The coverage is obtained from the following formula by using X1 and X2.
[0213] Fatty acid metal salt coverage E (%) = X1 / X2 × 100
[0214] Determination of the amount D of external additive B
[0215] The amount of external additive B was measured by using a wavelength dispersive X-ray fluorescence analyzer "Axios" (manufactured by PANalytical) and attached dedicated software "SuperQ ver.4.0F" (manufactured by PANalytical) for setting measurement conditions and analyzing measurement data. Rh was used as the anode of the X-ray tube, the measurement atmosphere was vacuum, the measurement diameter (collimator mask diameter) was 27 mm, and the measurement time was 10 seconds. In addition, when measuring light elements, detection was performed with a proportional counter (PC), and when measuring heavy elements, detection was performed with a scintillation counter (SC).
[0216] Pellets obtained by placing 4 g of toner in a dedicated aluminum ring for pressing, flattening, pressing at 20 MPa for 60 seconds using a tablet forming press "BRE-32" (manufactured by Maekawa Test Machine Co., Ltd.) and forming into a thickness of 2 mm and a diameter of 39 mm are used as measurement samples.
[0217] For example, when the external additive B is a zinc salt of a fatty acid, 0.1 parts by mass of zinc oxide (ZnO) fine powder is added to 100 parts by mass of toner particles containing no external additive, and is thoroughly mixed using a coffee mill. Similarly, 1.0 parts by mass and 5.0 parts by mass of silica fine particles are mixed with toner particles, respectively, and these are used as samples for the calibration curve.
[0218] For each sample, pellets of the sample for calibration curve were prepared using a tablet forming press as described above, and the Zn-Kα ray count rate (unit: cps) observed at a diffraction angle (2θ) = 109.08° when PET was used as a spectroscopic crystal was measured. At this time, the acceleration voltage and current value of the X-ray generator were set to 24 kV and 100 mA, respectively. A calibration curve of a linear function was obtained by plotting the obtained X-ray count rate as the ordinate and the amount of ZnO added in each calibration curve sample as the abscissa.
[0219] Then, the toner to be analyzed is granulated using a tablet forming press as described above, and the Zn-Kα ray count rate is measured. Then, the amount of the external additive (fatty acid metal salt) in the toner is determined from the above calibration curve.
[0220] Coverage of external additive A (silica fine particles)
[0221] The coverage of the toner surface with the external additive is calculated as follows.
[0222] The following apparatus was used under the following conditions, and elemental analysis of the toner surface was performed.
[0223] - Measurement device: Quantum 2000 (trade name, manufactured by ULVAC-PHI Co., Ltd.)
[0224] -X-ray source: monochromatic Al Kα
[0225] -X-ray setting: 100μmφ(25W(15KV))
[0226] -Photoelectron emission angle: 45 degrees
[0227] - Neutralization conditions: Use a neutralizing gun and an ion gun together
[0228] -Analysis area: 300μm×200μm
[0229] -Transfer energy: 58.70eV
[0230] - Step size: 0.125eV
[0231] -Analysis software: Multipak (PHI)
[0232] For example, the following describes a case where the external additive includes silica fine particles. In determining the coverage, the quantitative value of Si atoms is calculated using the peaks of C1s (BE 280 eV to 295 eV), O 1s (BE 525 eV to 540 eV), and Si 2p (BE 95 eV to 113 eV).
[0233] The quantitative value of Si atoms obtained here is represented by Y1.
[0234] Then, elemental analysis of the silica particles alone is performed in the same manner as in the above-mentioned elemental analysis of the toner surface, and the quantitative value of Si atoms obtained here is represented by Y2.
[0235] The coverage X1 of the silica fine particles on the toner surface is defined by the following formula using the above Y1 and Y2:
[0236] X1(%)=(Y1 / Y2)×100.
[0237] The same sample was measured 100 times and the arithmetic mean was used.
[0238] In obtaining the quantitative value Y2, when an external additive for external addition is available, measurement may be performed using the external additive.
[0239] When the external additive separated from the surface of the toner particles is used as a measurement sample, the external additive is separated from the toner particles by the following method.
[0240] A total of 160 g of sucrose (manufactured by Kishida Chemical Co., Ltd.) was added to 100 mL of ion exchange water and dissolved while heating in a water bath to prepare a concentrated sucrose solution. A total of 31 g of the concentrated sucrose solution and 6 mL of CONTAMINON N were placed in a centrifuge tube to prepare a dispersion. To the dispersion, 1 g of a toner was added and lumps of the toner were dispersed with a spatula or the like.
[0241] The centrifuge tube was shaken for 20 minutes at 350 reciprocating motions per minute in a shaker ("KM Shaker", manufactured by Iwaki Sangyo Co., Ltd.). After shaking, the solution was transferred to a glass tube (50 mL) for a swing rotor and centrifuged at 58.33 s / min in a centrifuge (H-9R, manufactured by Kokusan Co., Ltd.). -1 The centrifugal separation was performed for 30 minutes under the conditions of . In the glass tube after the centrifugation, the toner was present in the uppermost layer, and the external additive was present in the aqueous solution side of the lower layer.
[0242] The aqueous solution of the lower layer is collected and centrifuged to separate sucrose and the external additive B and collect the external additive. The centrifugation is repeated as necessary, and after sufficient separation, the dispersion is dried and the external additive is collected.
[0243] When a plurality of external additives are used, a target external additive may be selected from the collected external additives by using a centrifugation method or the like.
[0244] Method for measuring the fixation rate F of the external additive A (silicon dioxide fine particles)
[0245] A total of 160 g of sucrose (manufactured by Kishida Chemical) was added to 100 mL of ion exchange water and dissolved in a water bath to prepare a concentrated sucrose solution. A total of 31 g of concentrated sucrose solution and 6 mL of CONTAMINON N (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments; pH 7 and including nonionic surfactants, anionic surfactants and organic detergents, manufactured by Wako Pure Chemical Industries, Ltd.) were placed in a centrifuge tube (capacity 50 mL) to prepare a dispersion. A total of 1.0 g of toner was added to the dispersion, and the lumps of the toner were dispersed with a scraper or the like.
[0246] The centrifuge tube was shaken for 20 minutes at 350 spm (strokes per min) in a shaker ("KM Shaker", manufactured by Iwaki Sangyo Co., Ltd.). After shaking, the solution was transferred to a glass tube for a swing rotor (capacity 50 mL) and separated at 3500 rpm for 30 minutes using a centrifuge (H-9R; manufactured by Kokusan Co., Ltd.).
[0247] It is visually confirmed that the toner and the aqueous solution are sufficiently separated, and the toner separated in the uppermost layer is collected with a scraper or the like.
[0248] The aqueous solution containing the collected toner was filtered with a vacuum filter and then dried with a dryer for more than 1 hour. The dried product was deagglomerated with a scraper, and the amount of silicon Si element was measured by X-ray fluorescence. The fixing rate (%) was calculated from the ratio of the element amount of the toner treated with the dispersion and the initial toner to be measured.
[0249] The fluorescent X-ray measurement of each element conforms to JIS K 0119-1969, and the details are as follows.
[0250] As the measuring apparatus, a wavelength dispersive X-ray fluorescence analyzer "Axios" (manufactured by PANalytical) and attached dedicated software "SuperQ ver.4.0F" (manufactured by PANalytical) for setting the measuring conditions and analyzing the measuring data were used. Rh was used as the anode of the X-ray tube, the measuring atmosphere was vacuum, the measuring diameter (collimator mask diameter) was 10 mm, and the measuring time was 10 seconds. When measuring light elements, a proportional counter (PC) was used, and when measuring heavy elements, a scintillation counter (SC) was used.
[0251] Pellets prepared by placing about 1 g of the toner treated with the dispersion or the initial toner in a 10 mm diameter aluminum ring for pressing, flattening, and forming into a thickness of about 2 mm by pressing with a tablet forming press "BRE-32" (Maekawa Testing Machine MFG Co., Ltd.) at 20 MPa for 60 seconds were used as measurement samples.
[0252] The measurement was performed under the above-mentioned conditions, the element was identified based on the obtained X-ray peak position, and the concentration thereof was calculated from the count rate (unit: cps) which is the number of X-ray photons per unit time.
[0253] As a quantitative method in the toner, for example, the amount of silicon is determined by adding 0.5 parts by mass of silica (SiO2) fine particles relative to 100 parts by mass of the toner particles and mixing them thoroughly using a coffee grinder. Similarly, silica fine particles are mixed with toner particles to obtain 2.0 parts by mass and 5.0 parts by mass, respectively, and they are used as samples for the calibration curve.
[0254] For each sample, pellets of the sample for calibration curve were prepared using a tablet forming press as described above, and the Si-Kα ray count rate (unit: cps) observed at a diffraction angle (2θ) = 109.08° when PET was used as a spectroscopic crystal was measured. At this time, the acceleration voltage and current value of the X-ray generator were set to 24 kV and 100 mA, respectively. A calibration curve of a linear function was obtained by plotting the obtained X-ray count rate as the ordinate and the amount of SiO2 added in each calibration curve sample as the abscissa.
[0255] Then, the Si-Kα count rate is measured using the pellets of the toner to be analyzed. Then, the amount of silicon in the toner is determined from the calibration curve. The ratio of the amount of silicon of the toner treated with the dispersion calculated by the above method to the initial amount of silicon of the toner is taken as the fixing rate (%).
[0256] Method for measuring the fixation rate of external additive B (fatty acid metal salt)
[0257] In the method for measuring the fixation rate of the external additive A, the element to be measured is an element contained in the fatty acid metal salt. For example, in the case of zinc stearate, zinc is the measurement target. In addition, the fixation rate of the fatty acid metal salt is measured by the same method.
[0258] Method for measuring the number average particle size of primary particles of external additive A
[0259] The number average particle diameter of primary particles of the external additive A (silica fine particles) was measured using a scanning electron microscope "S-4800" (trade name; manufactured by Hitachi, Ltd.).
[0260] The toner to which the external additive has been externally added is observed, and the number average particle diameter is obtained by measuring the major diameters of 100 randomly selected primary particles of the external additive A in a visual field magnified to 50000 times. The observation magnification is appropriately adjusted according to the size of the external additive.
[0261] The external additive A and the external additive B (fatty acid metal salt) can be distinguished from each other by their appearance using a scanning electron microscope.
[0262] Method for measuring melting point of wax and glass transition temperature Tg of toner particles
[0263] The melting point of the wax and the glass transition temperature Tg of the toner particles were measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) according to ASTM D3418-82. The temperature correction of the device detection unit used the melting points of indium and zinc, and the heat correction used the heat of fusion of indium.
[0264] Specifically, about 3 mg of the sample (wax, toner particles) was accurately weighed and placed in an aluminum pan, and an empty aluminum pan was used as a reference. The measurement was performed at a temperature increase rate of 10°C / min in a measurement temperature range of 30°C to 200°C. In the measurement, the temperature was once increased to 200°C at a rate of 10°C / min, then decreased to 30°C at a rate of 10°C / min, and then increased again at a rate of 10°C / min.
[0265] The physical properties were determined using the DSC curve obtained during the second temperature increase. In the DSC curve, the temperature of the maximum endothermic peak of the DSC curve in the temperature range of 30°C to 200°C was defined as the melting point of the sample. In the DSC curve, the intersection between the line at the midpoint of the baseline before and after the specific heat change and the DSC curve was defined as the glass transition temperature Tg.
[0266] Determination of average circularity of toner particles
[0267] The average circularity of the toner particles is determined using a "FPIA-3000" flow-type particle image analyzer (Sysmex Corporation) under measurement and analysis conditions for calibrated operation.
[0268] The specific measurement method is as follows.
[0269] About 20 mL of ion exchange water from which solid impurities and the like had been removed was first placed in a glass container. Then, about 0.2 mL of a dilution of "Contaminon N" (a 10% by mass aqueous solution of a neutral detergent at pH 7 for cleaning precision measuring devices, including a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion exchange water was added.
[0270] Then about 0.02 g of the measurement sample is added and dispersed with an ultrasonic disperser for 2 minutes to obtain a measurement dispersion liquid. Cooling is appropriately performed during this process so that the dispersion liquid temperature is 10°C to 40°C.
[0271] Using a table-top ultrasonic cleaner and disperser having an oscillation frequency of 50 kHz and a power output of 150 W, a specific amount of ion-exchanged water was placed in the disperser water tank, and about 2 mL of Contaminon N was added to the tank.
[0272] A flow type particle image analyzer equipped with a "LUCPLFLN" objective lens (magnification 20x, aperture 0.40) was used for the measurement, and a particle sheath "PSE-900A" (Sysmex Corporation) was used as a sheath liquid. The dispersion obtained by the above method was introduced into the flow type particle image analyzer, and 2000 toner particles were measured in the HPF measurement mode, the total count mode.
[0273] Then, the average circularity of the toner particles is determined during particle analysis with a binarization threshold of 85% and limiting the analyzed particle size to an equivalent circle diameter of at least 1.977 μm to less than 39.54 μm.
[0274] Before the start of measurement, automatic focus adjustment is performed using standard latex particles (e.g., Duke Scientific Corporation "RESEARCH AND TEST PARTICLES Latex Microsphere Suspensions 5100A" diluted with ion-exchanged water). Then, automatic focus adjustment is performed again every 2 hours after the start of measurement.
[0275] Example
[0276] The present invention is described in more detail below based on Examples and Comparative Examples, but the present invention is by no means limited thereto. Unless otherwise specifically stated, the parts in the examples are based on mass.
[0277] [Production Example of Toner Particles]
[0278] Production Example of Toner Particles 1
[0279] The following is a description of a production example of toner particles 1.
[0280] Preparation of resin particle dispersion
[0281] 89.5 parts of styrene, 9.2 parts of butyl acrylate, 1.3 parts of acrylic acid and 3.2 parts of n-lauryl mercaptan were mixed and dissolved. 1.5 parts of Neogen RK (DKS Co., Ltd.) in an aqueous solution in 150 parts of ion exchange water were added and dispersed. Then slowly stirred for 10 minutes, while adding 0.3 parts of potassium persulfate in an aqueous solution in 10 parts of ion exchange water. After nitrogen purging, emulsion polymerization was carried out at 70°C for 6 hours. After the polymerization was completed, the reaction solution was cooled to room temperature, and ion exchange water was added to obtain a resin particle dispersion having a volume-based median particle size of 0.2 μm and a solid concentration of 12.5% by mass.
[0282] Preparation of release agent dispersion
[0283] 100 parts of a release agent (behenyl behenate, melting point 72.1° C.) and 15 parts of Neogen RK were mixed with 385 parts of ion exchange water and dispersed for about 1 hour using a wet jet mill unit JN100 (Jokoh Co., Ltd.) to obtain a release agent dispersion. The solid concentration of the release agent dispersion was 20% by mass.
[0284] Preparation of colorant dispersants
[0285] 100 parts of carbon black as a colorant "Nipex35 (Orion Engineered Carbons)" and 15 parts of Neogen RK were mixed with 885 parts of ion exchange water and dispersed for about 1 hour using a wet jet mill unit JN100 to obtain a colorant dispersion.
[0286] Preparation of toner particles 1
[0287] 265 parts of the resin particle dispersion, 10 parts of the release agent dispersion and 10 parts of the colorant dispersion were dispersed using a homogenizer (Ultra-Turrax T50, IKA). While stirring, the temperature in the container was adjusted to 30°C, and 1 mol / L hydrochloric acid was added to adjust the pH to 5.0. After leaving for 3 minutes, the temperature was started to rise, and the temperature was raised to 50°C to generate aggregated particles.
[0288] The particle size of aggregated particles was measured under these conditions using a "Multisizer(R) 3 Coulter Counter" (Beckman Coulter, Inc.) Once the weight average particle size reached 6.2 μm, a 1 mol / L sodium hydroxide aqueous solution was added to adjust the pH to 8.0 and terminate particle growth.
[0289] The temperature was then raised to 95° C. to fuse and spheroidize the aggregated particles. When the average circularity reached 0.980, the temperature was started to drop, and the temperature was lowered to 30° C. to obtain a toner particle dispersion 1.
[0290] The pH of the obtained toner particle dispersion 1 was adjusted to 1.5 or less by adding hydrochloric acid, and the dispersion was stirred for 1 hour, allowed to stand, and then subjected to solid-liquid separation in a filter press to obtain a toner filter cake. The toner was slurried with ion exchange water, redispersed, and subjected to solid-liquid separation in the aforementioned filter unit. The reslurrying and solid-liquid separation were repeated until the conductivity of the filtrate was no greater than 5.0 μS / cm, until a solid-liquid separated toner filter cake was finally obtained.
[0291] The obtained toner cake was dried with a flash jet dryer (gas dryer) (Seishin Enterprise Co., Ltd.). The drying conditions were that the blast temperature was 90°C and the dryer outlet temperature was 40°C, and the toner cake supply rate was adjusted according to the water content of the toner so that the outlet temperature did not deviate from 40°C. The fine powder and the coarse powder were shredded with a multi-stage classifier using the Coanda effect to obtain toner particles 1. Table 1 shows various physical properties.
[0292] Production Example of Toner Particles 2
[0293] Toner Particles 2 were obtained in the same manner as in the Production Example of Toner Particles 1 except that the particle growth stop time in the generation step of aggregated particles in the Production Example of Toner Particles 1 was changed. Table 1 shows various physical properties.
[0294] [Table 1]
[0295]
[0296] [Production Example of Fatty Acid Metal Salt]
[0297] Preparation Example of Fatty Acid Metal Salt 1
[0298] A receiving container equipped with a stirrer was prepared, and the stirrer was rotated at 350 rpm. 500 parts of a 0.5 mass % aqueous solution of sodium stearate was placed in the receiving container, and the liquid temperature was adjusted to 85° C. Then 525 parts of a 0.2 mass % aqueous solution of zinc sulfate was added dropwise to the receiving container over a period of 15 minutes. After all additions were completed, it was cured at the same temperature as the reaction for 10 minutes to terminate the reaction.
[0299] The fatty acid metal salt slurry thus obtained was filtered and washed. The washed fatty acid metal salt filter cake obtained was crushed and dried at 105°C using a continuous instantaneous air dryer. Then, the mixture was pulverized using a Nano Grinding Mill NJ-300 (Sunrex Industry Co., Ltd.) at 6.0 m 3 The mixture was crushed at a processing rate of 80 kg / hour at an air volume of 1.5 0.1 / min. The mixture was re-pulped and fine and coarse particles were removed by wet centrifugation. The mixture was then dried at 80°C by a continuous instantaneous air dryer to obtain a dry fatty acid metal salt 1.
[0300] The obtained fatty acid metal salt 1 had a volume-based median particle size (D50s) of 0.45 μm and a span value B of 0.92. Table 2 shows the physical properties of the fatty acid metal salt 1.
[0301] Preparation of fatty acid metal salt 2
[0302] In the production of fatty acid metal salt 1, a 1.0 mass % aqueous solution of sodium stearate was used instead of a 0.5 mass % aqueous solution of sodium stearate, and a 0.7 mass % aqueous solution of calcium chloride was used instead of a 0.2 mass % aqueous solution of zinc sulfate. The reaction was terminated by aging for 5 minutes. In addition, the pulverization conditions were changed to 5.0 m 3 / min of air volume, and after pulverization, fine powder and coarse powder were removed by a wind classifier to obtain fatty acid metal salt 2.
[0303] The obtained fatty acid metal salt 2 had a volume-based median particle size (D50s) of 0.58 μm and a span value B of 1.73. Table 2 shows the physical properties of the fatty acid metal salt 2.
[0304] Preparation of fatty acid metal salt 3
[0305] Fatty acid metal salt 3 was obtained in the same manner as in the production of fatty acid metal salt 1, except that 0.3 mass % aqueous solution of lithium chloride was used instead of 0.2 mass % aqueous solution of zinc sulfate.
[0306] The obtained fatty acid metal salt 3 had a volume-based median particle size (D50s) of 0.33 μm and a span value B of 0.85. Table 2 shows the physical properties of the fatty acid metal salt 3.
[0307] Preparation of fatty acid metal salt 4
[0308] Fatty acid metal salt 4 was obtained in the same manner as in the production of fatty acid metal salt 1, except that 0.5 mass % aqueous solution of sodium laurate was used instead of 0.5 mass % aqueous solution of sodium stearate.
[0309] The volume-based median particle size (D50s) of the obtained fatty acid metal salt 4 was 0.62 μm, and the span value B was 1.05. Table 2 shows the physical properties of the fatty acid metal salt 4.
[0310] Preparation of fatty acid metal salt 5
[0311] The 0.5 mass % aqueous solution of sodium stearate was replaced by a 0.25 mass % aqueous solution of sodium stearate, the 0.2 mass % aqueous solution of zinc sulfate was replaced by a 0.15 mass % aqueous solution of zinc sulfate, and the pulverization conditions were changed to an air volume of 10.0 m 3 / min and the number of pulverization steps was changed to 3 times, and fatty acid metal salt 5 was obtained in the same manner as in the production of fatty acid metal salt 1.
[0312] The volume-based median particle size (D50s) of the obtained fatty acid metal salt 5 was 0.18 μm, and the span value B was 1.34. Table 2 shows the physical properties of the fatty acid metal salt 5.
[0313] Fatty acid metal salt 6
[0314] Commercially available zinc stearate (MZ2, manufactured by NOF Corporation) was used as fatty acid metal salt 6. The volume-based median particle size (D50s) was 1.29 μm, and the span value B was 1.61. Table 2 shows the physical properties of fatty acid metal salt 6.
[0315] Fatty acid metal salt 7
[0316] Commercially available zinc stearate (SZ2000, manufactured by Sakai Chemical Industry Co., Ltd.) was used as fatty acid metal salt 7. The volume-based median particle size (D50s) was 5.30 μm, and the span value B was 1.84. Table 2 shows the physical properties of fatty acid metal salt 7.
[0317] [Table 2]
[0318]
[0319] Silica fine particles
[0320] The following silica particles were used.
[0321] Silica fine particles 1
[0322] A total of 100 parts of dry silica fine powder (BET specific surface area of 300 m 2 / g] for hydrophobization.
[0323] Silica fine particles 2
[0324] A total of 100 parts of dry silica fine powder (BET specific surface area of 150 m2) was treated with 20 parts of dimethyl silicone oil. 2 / g] for hydrophobization.
[0325] Silica fine particles 3
[0326] A total of 100 parts of dry silica fine powder (BET specific surface area of 90 m 2 / g] for hydrophobization.
[0327] Silicon dioxide fine particles 4
[0328] A total of 100 parts of dry silica fine powder (BET specific surface area of 50 m 2 / g] for hydrophobization.
[0329] Production Example of Toner 1
[0330] First, as a mixing step 1, toner particles 1 and silica fine particles 2 are mixed using an FM mixer (FM10C model, manufactured by Nippon Coke Industry Co., Ltd.).
[0331] While the water temperature inside the jacket of the FM mixer was stabilized at 40°C ± 1°C, 100 parts of toner particles 1 and 2.0 parts of silica fine particles 2 were added. Mixing was started when the peripheral speed of the rotating blade was 38 m / sec, and mixing was performed for 10 minutes while controlling the water temperature and flow rate inside the jacket so that the water tank temperature was stabilized at 40°C ± 1°C to obtain a mixture of toner particles 1 and silica fine particles 2.
[0332] Thereafter, in the mixing step 2, the fatty acid metal salt 1 is added to the mixture of the toner particles 1 and the silica fine particles 2 by using an FM mixer (FM10C model, manufactured by Nippon Coke Industry Co., Ltd.). While the water temperature in the jacket of the FM mixer is stabilized at 25° C.±1° C., 0.2 parts of the fatty acid metal salt 1 is added to 100 parts of the toner particles 1.
[0333] Mixing was started when the peripheral speed of the rotating blade reached 20 m / sec, and the water temperature and flow rate in the jacket were controlled while mixing for 5 minutes so that the temperature in the water tank was stabilized at 25°C ± 1°C, and then sieved with a sieve having an opening of 75 μm to obtain toner 1. Table 3 shows the production conditions of toner 1, and Table 4 shows its physical properties.
[0334] [Table 3]
[0335]
[0336] In the table, “C.” means “comparison” and “T.” means “temperature”.
[0337] Production Examples of Toners 2 to 18 and Comparative Toners 1 to 6
[0338] Toners 2 to 18 and Comparative Toners 1 to 6 were obtained in the same manner as in the Production Example of Toner 1, except that the toner particles in the Production Example of Toner 1, the materials added in Mixing Step 1 and Mixing Step 2 and the number of additions, and the mixing conditions were changed as shown in Table 3.
[0339] In Toner 16, 0.2 parts of a hydrotalcite compound (DHT-4A, manufactured by Kyowa Chemical Industry Co., Ltd.) was used relative to 100 parts of the toner particles. Table 4 shows the physical properties.
[0340] [Table 4]
[0341]
[0342] In the table, "particle size" indicates the number average particle size of primary particles, and "C." indicates "comparative".
[0343] Examples 1 to 18, Comparative Examples 1 to 6
[0344] The obtained Toners 1 to 18 and Comparative Toners 1 to 6 were evaluated by the evaluation methods described below. Table 5 shows the evaluation results.
[0345] LBP evaluation
[0346] A modified version of the commercially available Canon laser printer LBP9950Ci was used. The modification involved changing the process speed to 330 mm / sec by changing the gears and software of the evaluation body, and also enabling printing with only the black station. The toner contained in the process cartridge of the LBP9950Ci was removed, the interior was cleaned by air blowing, and 150 g of the toner to be evaluated was loaded.
[0347] Then, the process box was left to stand for 24 hours in a normal temperature and humidity NN (25°C / 50%RH) environment. The process box after standing was attached to the LBP9950Ci black workstation. An image was printed 10,000 times at a 1.0% print rate in the horizontal direction of A4 paper in a normal temperature and humidity NN (25°C / 50%RH) environment.
[0348] After printing 10,000 times, the following evaluation was performed.
[0349] Evaluation of cleanliness
[0350] Print 5 sheets with 0.2mg / cm 2 The halftone images with a toner load of 1000 g were visually evaluated according to the following criteria. C or above was considered satisfactory.
[0351] A: No cleaning defects, no charging roller contamination.
[0352] B: No cleaning defects, charging roller contaminated.
[0353] C: Some cleaning defects can be confirmed on the halftone image.
[0354] D: There are noticeable cleaning defects on the halftone image.
[0355] Evaluation of retransferability
[0356] A cartridge without black toner was set in the black station, and a cartridge after outputting 10,000 images was set in the cyan station. Then, the developing voltage was adjusted so that the toner bearing amount on the photosensitive member was 0.60 mg / cm2 Then, the toner of the photosensitive member re-transferred to the black station box was stuck with Mylar tape and peeled off.
[0357] By attaching to XEROX 4200 paper (75g / m 2 The reflectivity difference is calculated by subtracting the reflectivity T0 of the clean tape attached to the paper from the reflectivity T1 of the peeled tape (made by XEROX). The following judgment is made based on the value of the reflectivity difference. The reflectivity is measured using REFLECTMETER MODEL TC-6DS manufactured by Tokyo Denshoku Co., Ltd. The smaller the value, the more re-transfer is prevented. C or above is considered satisfactory.
[0358] Evaluation Criteria
[0359] A: The reflectance difference is 2.0% or less.
[0360] B: The reflectance difference is more than 2.0% and 5.0% or less.
[0361] C: The reflectance difference is more than 5.0% and 10.0% or less.
[0362] D: The reflectance difference is greater than 10.0%.
[0363] Evaluation of Development Streaks
[0364] The number of vertical streaks that appeared on the developing roller after printing images 10,000 times was evaluated according to the following criteria: C or above was considered satisfactory.
[0365] Evaluation Criteria
[0366] A: No vertical streaks are visible on the developer roller.
[0367] B: Three or less thin stripes are observed in the circumferential direction at both ends of the developing roller.
[0368] C: 4 to 10 thin stripes in the circumferential direction are seen at both ends of the developing roller.
[0369] D: Eleven or more streaks were seen on the developing roller.
[0370] Fogging evaluation
[0371] After outputting the above 10,000 images, one solid white image was output, and the obtained solid white image was evaluated for fogging. The fogging density (%) was measured using "REFLECTMETER MODEL TC-6DS" (manufactured by Tokyo Denshoku Co., Ltd.) and calculated from the difference between the whiteness of the white background portion of the measured image and the whiteness of the transfer paper.
[0372] Use a green filter. C and above are considered satisfactory.
[0373] Evaluation Criteria
[0374] A: The fogging concentration is less than 0.5%.
[0375] B: The fogging concentration is 0.5% or more and less than 1.0%.
[0376] C: The fogging concentration is 1.0% or more and less than 2.0%.
[0377] D: The fogging concentration is 2.0% or more.
[0378] [Table 5]
[0379] Toner Cleanability Retransferability Fogging Development stripes Example 1 Toner 1 A A B A Example 2 Toner 2 A A B A Example 3 Toner 3 A C B A Example 4 Toner 4 A C B A Example 5 Toner 5 A A A A Example 6 Toner 6 A B C C Example 7 Toner 7 C A A A Example 8 Toner 8 A B B A Example 9 Toner 9 A C B A Example 10 Toner 10 A C B C Embodiment 11 Toner 11 A B B A Example 12 Toner 12 B C B A Embodiment 13 Toner 13 B C B A Embodiment 14 Toner 14 A A B A Embodiment 15 Toner 15 A A B B Example 16 Toner 16 A A A A Embodiment 17 Toner 17 A C B B Embodiment 18 Toner 18 C B B C Comparative Example 1 Compare Toner 1 A D C A Comparative Example 2 Compare Toner 2 A D C A Comparative Example 3 Compare Toner 3 D B B A Comparative Example 4 Compare Toner 4 A D D D Comparative Example 5 Compare Toner 5 B D C A Comparative Example 6 Compare Toner 6 C D D B
[0380] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner, characterized in that include: Toner particles containing a binder resin; and External additives, among which The external additive includes an external additive A and an external additive B, and the external additive further includes a hydrotalcite compound, The external additive A is silica fine particles, The external additive B is a fatty acid metal salt, The external additive A has a primary particle number average particle size of 5 nm to 25 nm, The coverage of the surface of the toner particles by the external additive A is 60% to 80%, and The average theoretical surface area obtained when the number average particle size, particle size distribution and true density of the toner particles measured by a Coulter counter is expressed in m 2 / g is represented by C, the amount of the external additive B relative to 100 parts by mass of the toner particles is represented by D in parts by mass, and the coverage of the surface of the toner particles by the external additive B is represented by E in %, the following formulas (1) and (2) are satisfied: 0.05≤D / C≤2.00…(1) E / (D / C)≤50.0…(2). 2 . The toner according to claim 1 , wherein a fixing rate F of the external additive A to the toner particles is 80% or more. 3 . The toner according to claim 1 , wherein a fixing rate G of the external additive B to the toner particles is 10% or less. 4 . The toner according to claim 1 , wherein the fatty acid metal salt comprises at least one selected from the group consisting of zinc stearate and calcium stearate. 5 . The toner according to claim 1 , wherein the fatty acid metal salt has a volume-based median particle diameter D50s of 0.15 μm to 2.00 μm. 6 . The toner according to claim 1 , wherein the relationship between a fixing rate F of the external additive A to the toner particles in % and a fixing rate G of the external additive B to the toner particles in % is F / G≧8.
0.
7. The toner according to claim 1 or 2, wherein the fatty acid metal salt has a span value B defined by the following formula (3) of 1.75 or less: Span value B = (D95s-D5s) / D50s (3), wherein D5s is the 5% cumulative diameter based on volume of the fatty acid metal salt, D50s is the 50% cumulative diameter on a volume basis of the fatty acid metal salt, and D95s is the 95% cumulative diameter on a volume basis of the fatty acid metal salt.
